Effect of Lactiplantibacillus and sea buckthorn pomace on the fermentation quality and microbial community of paper mulberry silage - Peng, Shun; Xie, Lingling; Cheng, Yuyao; Wang, Qiqi; Feng, Li; Li, Yang; Lei, Yonghui; Sun, Yanfei (Frontiers in Plant Science, 2024)
Background: Paper mulberry is a promising alternative fodder source due to their high protein and the abundance of active components. However, paper mulberry often faces susceptibility to contamination during silage fermentation, and there is a need to improve the quality of silage fermentation of paper mulberry through exotic additives. Sea buckthorn pomace (BP) is a feed additive containing antimicrobial and antioxidant substances that help to enhance silage fermentation. Therefore, the objective of this study was to evaluate the effects of BP and Lactiplantibacillus as additives on silage fermentation and bacterial community of paper mulberry.The results showed that BP and Lactiplantibacillus significantly reduced the pH and ammonium nitrogen content of paper mulberry silage (P < 0.05) and significantly increased the content of lactic acid and acetic acid (P < 0.05), resulting in more residual water soluble carbohydrate and crude protein contents and less fiber content in relative to control. The key microorganisms in paper mulberry silage fermentation are Lactiplantibacillus pentosus and Weissella cibaria. Among them, Lactiplantibacillus favoured a rapid increase in Lactiplantibacillus pentosus abundance during the pre-silage fermentation period, whereas BP favoured the promotion of Lactiplantibacillus pentosus growth, resulting in higher contents of lactic and acetic acid than those of the control.Simultaneously adding Lactiplantibacillus and BP can effectively improve the quality of paper mulberry silage and increase the abundance of beneficial microorganisms in paper mulberry silage.